Silibinin Inhibit Cell Migration through Downregulation of RAC1 Gene Expression in Highly Metastatic Breast Cancer Cell Line - Lashgarian, Hamed Esmaeil; Adamii, Vahid; Ghorbanzadeh, Vajihe; Chodari, Leila; Kamali, Fayze; Akbari, Soheila; Dariushnejad, Hassan (Drug Research, 2020)
Background Triple negative breast cancer is the most invasive breast cancer subtype and possesses poor prognosis and survival. Rho GTPase famil, especially Rac1 participates in a number of signaling events in cells with crucial roles in malignancy, migration and invasion of tumor cells. Silibinin, a flavonoid antioxidant from milk thistle has attracted attention in the recent decades for chemoprevention and chemotherapy of tumor cells. In this study, the effect of silibinin on the migration capacity of MDA-MB-231 cells, a highly metastatic human breast cancer cell line was investigated by evaluation of Rac1 expression.Method MTT wound healing and transwell assays were performed to evaluate the effects of silibinin on proliferation and migration of MDA-MB-231 cells. In addition, the influence of the silibinin on the expression of Rac1mRNAs was assessed by RT-PCR.Results Results indicated significant dose-dependent inhibitory effect of silibinin on proliferation and migration of MDA-MB-231 cells. It significantly inhibited the expression of Rac1 mRNA.Conclusion In conclusion, the results demonstrate that the silibinin can be used as an experimental therapeutic for the management of TNBC metastatic cancer.
Keywords: silibinin; breast cancer; TNBC; Rac1; metastasis